The Influence of Ecological Leadership and Organizational Culture on Pro Environtmental Behaviors: The Mediating Employee Environmental Empowerment - Adhiati, Sekarini; Ratnawati, Intan (Management Analysis Journal, 2021)
The aim of this study was to analyze the extent to which a company implement environment-based sustainable improvement. In modern era, many companies put emphasis on improving economic sector while ignoring environmental sustainability. The faster the industrial growth in Indonesia is, the more waste it generates. Thus, in order to increase pro-environmental behavior at PT Telekomunikasi Indonesia Regional Division IV Central Java and Yogyakarta, it is necessary to have leaders who adopt ecological leadership and organizational culture models. Therefore, the specific aim of the study was to determine the role of employee environmental empowerment in this company. The results showed that ecological leadership and organizational culture had a positive and significant effect on employee environmental empowerment and pro-environmental behavior. Employee environmental empowerment had a positive and significant effect on pro-environmental behavior. Meanwhile, as the total effect on ecological leadership had the highest effect value, the ecological leadership was the main key of this company. This suggests that the function of the ecological leadership has to be maintained and its quality has to be improved so that employees have a role model who is able to motivate and generate a spirit of caring for the environmental issues in the company.